IMPLEMENTASI PEMBELAJARAN FIKIH LOKAL DI MA TANBIHUL GHOFILIN, BAWANG, BANJARNEGARA - Hikmah, Isma Kholifatun (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2025)
The development of the times demands that the younger generation be able to adapt to the continuously evolving issues of Islamic jurisprudence (fiqh). This study aims to examine the implementation of local fiqh learning at MA Tanbihul Ghofilin, Bawang, Banjarnegara, covering the understanding of concepts, learning sources, curriculum, learning processes (preparation, implementation, and evaluation), as well as its benefits for students. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The validity of the data was tested using triangulation techniques. Data were analyzed using the interactive model of Miles and Huberman, which includes data collection, reduction, presentation, and conclusion drawing. The research results show that: 1) Local fiqh learning uses the Fathul Qorib textbook with the traditional bandongan method of pesantren, emphasizing the practical application of Islamic law in daily life; 2) The learning stages consist of systematic preparation, implementation, and evaluation; and 3) Local fiqh learning plays an essential role in enhancing students’ religious understanding, shaping their moral and spiritual character, and preparing them to become future generations capable of addressing fiqh-related issues in society. The implication of this study is that local fiqh serves as a relevant and contextual learning model for modern Islamic schools (madrasahs).